A study of Tetranychus urticae Koch resistance to the ovicidal acaricides clofentezine and hexythiazox in South African pome fruit orchards - Hodges, G.(Garth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.